(untitled) (Research, Society and Development, 2019)
This study aimed to verify the main difficulties, access and use of digital media for students of two higher education courses, being a night technologist, and a bachelor of engineering full time. For validation, a quantitative approach research was conducted through the application of a questionnaire, the results are organized and presented in graphs. We observed that students use their mobile phone mainly to access social networks, email, listen to music and take pictures, while the computer is used for formatting texts, images, spreadsheets and presentations. Another point observed is that students who study full time pointed to access to the Internet as the greatest difficulty, while at night, the main one was technical knowledge.